Serum 17β-estradiol inversely correlates with circulating group 2 innate lymphoid cells in a cohort of asthmatic patients - Elizabeth J. Myers; Elizabeth J. Myers; Samuel E. Aamodt; Samuel E. Aamodt; Thomas P. Huecksteadt; Robert Paine; Robert Paine; Mustafa Mir-Kasimov; Mustafa Mir-Kasimov; Christopher A. Reilly; Sean J. Callahan; Sean J. Callahan; et al. (Frontiers in Immunology, 2025)
IntroductionAsthma is a chronic airway inflammatory disorder that demonstrates a strong clinical bias in females of reproductive age. In this study we evaluated group 2 innate lymphoid cells (ILC2) that play a now well-defined role in allergy and asthma. ILC2 are rare immune cells that demonstrate a strong activation bias in females compared to males in both mice and humans. We hypothesized that ILC2 would be highly activated in people with asthma as compared to healthy, sex-matched controls.MethodsSubjects with asthma were identified by medical records searching and confirmed through pre-clinic interviews regarding asthma diagnosis. Additional demographic and clinical data were collected from study questionnaires or retrospective chart review. Correlations were determined between immune activation and hormone levels for each study participant regardless of healthy or asthma status.ResultsResults showed that within the asthma groups, female Veterans had higher circulating blood neutrophils compared to males, and males had higher eosinophils compared to females by complete blood cell count. ILC2 trended upwards in male Veterans with asthma compared to female Veterans with asthma (p = 0.086). Females with asthma had a marked reduction in CRTH2+ ILC2 in comparison to healthy female controls. The numbers of ILC2 in correlation to ovarian hormones were determined to show a significant inverse correlation with estrogen levels and ILC2 suggesting that estrogen may suppress ILC2 abundance in circulation.ConclusionsAdditional studies are necessary to determine whether this estrogen-effect extends to the lung and airways of people with asthma.